Electrochemical behaviour of graphene and alumina whisker co-reinforced copper matrix composites. (17th February 2023) - Shao, Zhenyi; Li, Xubo; Wei, Yanhong; Chen, Jianrun; Qin, Qing; Xian, Yong; Ding, Yichao
ABSTRACT : This study prepared copper (Cu) matrix composites with different graphene contents (0∼1.0 wt-%) and an equal amount of alumina (Al2 O3 ) whisker by vacuum hot pressing sintering. The microstructures of the Cu/C and Cu/Al2 O3 interfaces were characterised. The electrochemical corrosion behaviour of the composites was evaluated to study the influence of graphene content on the corrosion performance of the Cu matrix composites. The results showed that incorporating uniformly dispersed graphene with a small amount (∼0.25 wt-%) enables close integration with the Cu matrix, slows down the corrosion rate, and increases the impedance of the composites, thus effectively improving the corrosion resistance of Cu matrix composites. With an increase in graphene content (∼1.0 wt-%), defects tend to generate, leading to the formation of multiple corrosive microcell cavities in the composite, thus accelerating the corrosion of the composite. The Gr/Cu-0.25 composite exhibited better corrosion resistance in acidic, neutral, and alkaline corrosive solutions.